2020
DOI: 10.5152/eurasianjmed.2019.19044
|View full text |Cite
|
Sign up to set email alerts
|

Do Resveratrol and Dehydroepiandrosterone Increase Diminished Ovarian Reserve?

Abstract: Aims and Scope Eurasian Journal of Medicine (Eurasian J Med) is an international, scientific, open access periodical published by independent, unbiased, and triple-blinded peer-review principles. The journal is the official publication of Atatürk University School of Medicine and published triannually in February, June, and October. The publication language of the journal is English. The aim of the Eurasian Journal of Medicine is to publish original research papers of the highest scientific and clinical value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Growing evidence indicates that resveratrol has potential effects in stimulating ovarian function and retarding ovarian aging. In POF animal models, induced by drugs, radiotherapy, or heavy metals, resveratrol significantly promotes primordial follicle activation, increases the number of primary, primordial, and growing follicles, stimulates GC proliferation, diminishes ovarian inflammation, maintains ovarian architecture, and rescues oocyte and GC apoptosis ( Banu et al, 2016 ; Said et al, 2016 ; Liu Y et al, 2017 ; Chinwe et al, 2018 ; Li and Liu, 2018 ; Ata et al, 2019 ; Said et al, 2019 ; Wu et al, 2019 ; Ozatik et al, 2020 ). Besides these features, long-term (12 months) oral administration of resveratrol can prevent telomere shortening, increase telomerase activity to increase the primary and growing follicles, increase the oocyte quantity and quality, and enhance embryonic development in aging mice to achieve anti-ovarian aging ( Liu et al, 2013 ).…”
Section: Natural Antioxidant-based Interventions To Reduce Oxidative mentioning
confidence: 99%
“…Growing evidence indicates that resveratrol has potential effects in stimulating ovarian function and retarding ovarian aging. In POF animal models, induced by drugs, radiotherapy, or heavy metals, resveratrol significantly promotes primordial follicle activation, increases the number of primary, primordial, and growing follicles, stimulates GC proliferation, diminishes ovarian inflammation, maintains ovarian architecture, and rescues oocyte and GC apoptosis ( Banu et al, 2016 ; Said et al, 2016 ; Liu Y et al, 2017 ; Chinwe et al, 2018 ; Li and Liu, 2018 ; Ata et al, 2019 ; Said et al, 2019 ; Wu et al, 2019 ; Ozatik et al, 2020 ). Besides these features, long-term (12 months) oral administration of resveratrol can prevent telomere shortening, increase telomerase activity to increase the primary and growing follicles, increase the oocyte quantity and quality, and enhance embryonic development in aging mice to achieve anti-ovarian aging ( Liu et al, 2013 ).…”
Section: Natural Antioxidant-based Interventions To Reduce Oxidative mentioning
confidence: 99%
“…StAR is known to govern the rate-limiting step in steroidogenesis, which is the translocation of cholesterol from the outer to the inner mitochondrial membrane ( Kiriakidou et al., 1996 ; Devoto et al., 2002 ). However, other studies demonstrated that RV depressed the AR transcriptional activity in cancer cells and in ovarian follicle ( Bowers et al., 2000 ; Ozatik et al., 2020 ). The discrepancies may due to the different animal type, stress model, and RV levels used the study.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, these resveratrolregulated processes affect the resistance of female reproductive system to adverse effects of environmental contaminants and reproductive and hormonal dysfunctions like reproductive aging, premature ovarian failure, polycystic ovarian syndrome, endometriosis and others. Details of possible functional interrelationships between particular signalling molecules and processes are not shown applicable in animal production, biotechnology and assisted reproduction for improvement culture of ovarian cell and tissues (Bezerra et al, 2018;Hao et al, 2018;Sirotkin, Alexa, et al, 2019;Sugiyama et al, 2015), prediction of success of oocyte in vitro fertilization (Liu et al, 2013;Wang, Su, et al, 2014;Sugiyama et al, 2015;B odis et al, 2019;Pasquariello et al, 2020), ovarian stimulation (Cabello et al, 2015), ovarian follicular growth and oocyte maturation (Kong et al, 2011;Wang, Su, et al, 2014;Sugiyama et al, 2015), embryo production (Wang, Su, et al, 2014;Pasquariello et al, 2020), oocyte and embryo cryoconservation (Pasquariello et al, 2020), improvement of laboratory (Kyselova et al, 2003;Li & Liu, 2018) and farm (Bal aži et al, 2019) animal reproductive traits and fertility and prevention of reproductive aging and exhaustion of ovarian follicular reserve (Li & Liu, 2018;Liu et al, 2013;Ozatik et al, 2020;Sugiyama et al, 2015).…”
Section: Application Of Rsv In Reproductive Biology and Medicinementioning
confidence: 99%